Integrating Climate Change into Road Asset Management - Henning, Theuns Frederick Phillip (World Bank, Washington, DC, 2017)
There is a wealth of scientific reports that records the actual climatic changes that have been taking place during recent years. While there is debate over the causes of climate change, the rate at which this phenomenon is increasing is overwhelming – with the evidence indicating that the changes in our environment will impact large parts of the globe. The Transport and ICT Global Practice (T and I) provides clients with physical and virtual connectivity solutions, to facilitate the movement of people, goods and information, thus enabling access to food, jobs, health and education services, and stimulating economic and social development. This report highlights some challenges to the research and academic fraternity in understanding climatic impacts on road networks better, developing more resilient technologies and, most importantly, developing a better understanding to quantify the impact or benefits of climate adaptation strategies. The main conclusion of this report is that asset management, when undertaken according to best practice, is already one of the most significant climate adaptation strategies. With minor adaption to existing asset management processes and techniques, a far greater return may be gained from investment to allow for changing demands on road infrastructure, both from a changing climate and from an ever-changing population. For more information, visit http://www.worldbank.org/en/topic/transport.